SpongeScapes: Understanding the role of nature-based solutions in improving sponge functioning of landscapes – the case of regenerative agriculture - Sah Neeraj; Blake James; D’Acunha Brenda; Bell Vicky; Evans Jon; Morrison Ross; Dussaillant Alejandro (E3S Web of Conferences)
The SpongeScapes project aims to accelerate understanding Nature-based Solutions (NBS) that enhance the sponge functioning of soil, groundwater, and surface water ecosystems, improving landscape resilience against hydrometeorological extremes across diverse climates. One NBS being explored within SpongeScapes is the adoption of Regenerative Agricultural Practices (RAPs) such as reduced tillage and cover cropping. These practices can improve soil health and potentially increase water retention capacity, compared to conventional agriculture practices that degrade soil structure and porosity. However, quantifying RAP benefits is challenging due to the delayed soil response to management changes. This report discusses an exploratory approach of back-analysing long-term soil moisture datasets to assess the impacts of RAPs on soil water retention capacity. By inferring changes in saturated water content (proxy for porosity), findings from trend analyses on UK case studies provide insights into the potential of RAPs as an NBS for enhancing landscape water resilience through improved soil sponge functioning.